SPEECH DISFLUENCY IN GROUPS PRESENTATIONS OF ENGLISH EDUCATION MASTERS PROGRAM STUDENTS - Sanjaya, Albertus Agung; Nugrahani, Veronica Esti (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2018)
English Education Master Program (EEMP) students are required to master listening, speaking, reading, and writing skills. Regarding the speaking skill, they must have fluency and clarity in speaking English since they should be good models for their students. However, the minimal use of English in their oral communication during the courses leads to the speech disfluency. They are aware of their disfluency but they do not understand the specific aspects of it. Thus, this study aimed to discuss the speech disfluency produced by the master students in oral communication. There was one formulated research question: What are the speech disfluencies which commonly occur in groups presentations among EEMP students? To examine the speech disfluencies, the researchers employed document analysis as the method of the study. The transcription of their groups presentations were analyzed based on the types of disfluency (Shriberg, 1994; Bailoor, John, Laxman, 2015). The findings showed that there were five disfluency types found in this study namely unfilled pause, filled pause, repetition, substitution, and deletion.